(untitled) (Physical Education, Health and Social Sciences, 2025)
The study explores how climate vulnerability affects life expectancy in Pakistan. Extreme climate events disrupt the life expectancy by increasing diseases and creating health problems, food insecurity and malnutrition, damage to health infrastructure, poor water quality and sanitation and displacement and living conditions. The study estimates the time series effect for the Pakistan economy using annual data from 1980 to 2024. The Augmented Dickey Fuller and Phillips Perron tests are first used to examine the stationarity of the data. The long-run relationship among the variables is then analysed using the Auto-Regressive Distributed Lag (ARDL) method, while the direction of influence is examined through the Granger causality test. The results reveal a stable long-term relationship between life expectancy and its key determinants. Rising income inequality, unemployment, poverty and growing climate vulnerability are found to significantly reduce life expectancy, indicating that unequal access to resources and increasing environmental stress place a serious burden on public health. In contrast, Health expenditure per capita and access to clean water contributes positively to life expectancy, suggesting that greater economic openness may improve living standards, healthcare access, and the availability of modern technologies. The causality analysis shows a one-way relationship running from income inequality, climate vulnerability, and globalization to life expectancy, confirming that social, economic, and environmental conditions play a leading role in shaping health outcomes in Pakistan. These findings highlight the need for policies that reduce economic disparities, strengthen resilience to climate risks, and promote inclusive health measures in order to improve life expectancy and overall well-being.